A MODEL OF DISCOVERY LEARNING BASED - TEXT BOOK OF CHARACTER AND ISLAMIC EDUCATION: AN ACCURACY ANALYSIS OF STUDENT BOOK IN ELEMENTARY SCHOOL - Fadriati Fadriati (Ta'dib, 2017)
This study aims at developing a valid discovery-learning text book for the Islamic Education (PAI) and Character subject delivered at the fifth grade of Primary School based on the results of the accuracy analysis of the existing student books. This is a Research and Development (R and D) applying the 4-D model proposed by Semmel and Thiagarajan, that is, defining, designing, developing, and disseminating. Data collection techniques used (1) instrument assessment with the format of student book analysis to measure the level of accuracy of the existing textbooks, (2) interviews and observations, conducted to the PAI teachers, and (3) validation sheets. Moreover, the technique of data analysis used inter rater analysis technique, known as the technique of intra class correlation coefficient analysis (Intraclass Correlation Coefficient-ICC). As the result, in terms of level of accuracy, the existing textbooks of Character and Islamic Education at the fifth grade of elementary school is still low. In general, the teachers claim that the existing text books are able to meet some of the basic competencies and indicators. However, the text books need to be refined and clarified the student learning activities, making it more simple for students to learn. On the other hand, the product of discovery learning textbooks on the subjects of Character and Islamic Education  at the fifth grade of elementary school are declared valid. This product is refined based on input, making it feasible for the students at the fifth grade of Primary School in learning Character and Islamic Education.